Tonality and the Cultural - Leech-Wilkinson, Daniel (Empirical Musicology Review, 2013)
The emphasis in this response to Mine Doğantan-Dack’s ‘Tonality: The Shape of Affect’ is on the cultural construction of tonality and the ways in which that may encourage Western musicians to understand tonality as a fundamental psychological process. An alternative hypothesis is proposed in which tonality assists in the effective musical modelling of hunting, offering a means to relive the experience in social groups.